Peningkatan Pengetahuan Kader Posyandu Dalam Pembuatan Makanan Tambahan Berbahan Dasar Pangan Lokal - Aziz, Fatmawati; Sunarto; Asikin, Hijrah (Universitas Sulawesi Barat, 2025)
Background: Stunting is a chronic nutritional problem that occurs over a long period and can be transmitted across generations. One of the key strategies to prevent stunting is providing adequate complementary feeding in both quality and quantity, as nutritional fulfillment plays a vital role in a child's growth. Nutrition education for Posyandu cadres serves as a strategic effort to enhance their role in stunting prevention.Objective: This study aimed to measure the effectiveness of nutrition education in improving cadres' knowledge regarding the preparation of supplementary food (PMT) using local food ingredients at Paccerakkang Public Health Center, Makassar City. Methods: This research used a quasi-experimental design with a one-group pre-test and post-test approach. A total of 30 Posyandu cadres were selected using quota sampling. Results: The findings showed that the average knowledge score increased from 5.77 (pre-test) to 9.83 (post-test). The paired sample t-test and Wilcoxon Signed Ranks Test indicated a statistically significant difference (p < 0.001), confirming that the training had a substantial impact on improving cadre knowledge. Conclusion: Training on the preparation of supplementary food based on local ingredients effectively enhances Posyandu cadres' knowledge and supports community-level efforts to prevent stunting.